2022
DOI: 10.1007/s11269-022-03302-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Whale Algorithm for Economic Load Dispatch Problem in Hydropower Plants and Comprehensive Performance Evaluation

Abstract: A novel method for economic load dispatch problem (ELDP) based on improved whale optimization algorithm(IWOA) is presented, and the optimization performance of IWOA in ELDP was evaluated comprehensively. The search mechanism is modi ed to improve the ability of the algorithm to jump out of the local optimal. The adaptive nonlinear inertia weight is introduced to improve the convergence speed of the algorithm. A limited mutation mechanism is proposed to improve the convergence of the algorithm. The evaluation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Later in the iteration, the magnitude of A, due to its own large step descent value, appears to be missing when it is necessary to mine hidden optimal solutions around the optimal solution. Therefore, inspired by the dynamic convergence factor in reference [20], this article proposes an improved nonlinear time-varying factor to improve a. This is used to compensate for the insufficient exploration ability in the early exploration phase of the the WOA and enhance its later development.…”
Section: Nonlinear Time-varying Factors and Inertia Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later in the iteration, the magnitude of A, due to its own large step descent value, appears to be missing when it is necessary to mine hidden optimal solutions around the optimal solution. Therefore, inspired by the dynamic convergence factor in reference [20], this article proposes an improved nonlinear time-varying factor to improve a. This is used to compensate for the insufficient exploration ability in the early exploration phase of the the WOA and enhance its later development.…”
Section: Nonlinear Time-varying Factors and Inertia Weightsmentioning
confidence: 99%
“…Shahraki et al [19] proposed a unique pooling mechanism and combined it with three effective search strategies to propose a binary improved whale optimization algorithm, which effectively solved the problem of COVID-19 medical detection. Yang et al [20] introduced adaptive nonlinear inertial weights into the WOA to control the convergence rate, and adopted the finite mutation mechanism to improve the convergence efficiency, showing superior performance in economic load scheduling problems. Shen et al [21] showed that, combined with the multi-population evolution strategy, WOAs have a unique global search ability and excellent ability to jump out of local optima, and have excellent performance in various engineering design problems.…”
Section: Introductionmentioning
confidence: 99%